The impact of neurological and cerebellar soft signs on psychosocial functioning in bipolar disorder - Chrobak, Adrian Andrzej; Soltys, Zbigniew; Starowicz-Filip, Anna; Styczeń, Krzysztof; Dec-Ćwiek, Małgorzata; Dudek, Dominika; Siwek, Marcin (Frontiers in Psychiatry, 2025)
BackgroundPatients with bipolar disorder (BD) present motor dysfunctions in the form of neurological and cerebellar soft signs (NSS and CSS, respectively). Little is known about the clinical utility of these symptoms and their impact on patients’ psychosocial functioning. The aim of our study is to assess the relationships between severity of NSS and CSS, as well as various dimensions of the daily functioning of patients with BD.MethodsA total of 100 participants were enrolled to this study: 60 patients with euthymic BD and 40 healthy controls (HC). Psychosocial functioning was evaluated with the use of Functioning Assessment Short Test (FAST) total score and its subscales. NSS were assessed with the use of the Neurological Evaluation Scale (NES). CSS were measured with the International Co-operative Ataxia Rating Scale (ICARS).ResultsGeneral psychosocial functioning was decreased by CSS and NSS severity represented by total NES and ICARS scores, as well as by higher measures of kinetic functions, sensory integration, motor coordination, and speech disorders subscales. Patients’ autonomy rates were decreased by total ICARS, kinetic functions, and speech disorders scores. Occupational functioning was limited by the majority of CSS and NSS measures. Cognitive functioning was associated with motor coordination impairments. Leisure time activities were influenced by total CSS severity and kinetic dysfunctions. We have shown that the severity of both CSS and NSS is a full mediator of the associations between duration of treatment and general psychosocial functioning.ConclusionsOur results suggest that even “soft” neurological abnormalities may have an impact on the psychosocial functioning of patients with BD.